2015
DOI: 10.1002/term.2103
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized biological matrices: an interesting approach for cardiovascular tissue repair and regeneration

Abstract: The repair and replacement of blood vessels is one of the most challenging topics for biomedical research. Autologous vessels are preferred as graft materials, but they still have many issues to overcome: for instance, they need multiple surgical procedures and often patients may not have healthy and surgically valuable arteries useful as an autograft. A tissue-engineering approach is widely desirable to generate biological vascular prostheses. Recently, decellularization of native tissue has gained significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 83 publications
0
32
0
1
Order By: Relevance
“…Emerging reports are showing the promising role of decellularized biological matrices for tissue repair (Boccafoschi et al, 2015). Our group has reported that WJ-MSCs conditioned-medium has positive effects on wound healing in human in vivo in full-thickness skin excisional wounds on a mouse model through paracrine signaling via several mechanisms: upregulation of wound healing factors' gene expression, such as TGF-ß2, HIF-1α and PAI-1 in addition to enhancing human skin fibroblasts proliferation and migration (Arno et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging reports are showing the promising role of decellularized biological matrices for tissue repair (Boccafoschi et al, 2015). Our group has reported that WJ-MSCs conditioned-medium has positive effects on wound healing in human in vivo in full-thickness skin excisional wounds on a mouse model through paracrine signaling via several mechanisms: upregulation of wound healing factors' gene expression, such as TGF-ß2, HIF-1α and PAI-1 in addition to enhancing human skin fibroblasts proliferation and migration (Arno et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has reported that WJ-MSCs conditioned-medium has positive effects on wound healing in human in vivo in full-thickness skin excisional wounds on a mouse model through paracrine signaling via several mechanisms: upregulation of wound healing factors' gene expression, such as TGF-ß2, HIF-1α and PAI-1 in addition to enhancing human skin fibroblasts proliferation and migration (Arno et al, 2014). It is known that the niche or microenvironment of stem cells is crucial in supporting the MSCs and that there is significant cross talk and signaling that occurs between the cells and the environment (Boccafoschi et al, 2015; Khodadi et al, 2016). Moreover, there is the secretome of stem cells which is within the Wharton's jelly.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is inherent to the use of synthetic ECM components needs to be thoroughly investigated. In addition, it seems that although most of the structure and composition of the scaffolds remain intact after decellularization, depending on the method of decellularization, the compliance, Young's Modulus, and stress–strain curves can decrease or increase, as reviewed by Boccafoschi et al…”
Section: Current and Novel Applications Of Membrane Technology In Kidmentioning
confidence: 99%
“…Common physical treatments involve sonication, pressure, shear forces, freezing and thawing 73 . Hypotonic and hypertonic solutions have also been found to be effective at mediating the cell lysing process 71 .…”
Section: Decellularization Strategiesmentioning
confidence: 99%
“…A wide variety of chemical treatments have been reported in the literature ranging from alkaline and acidic solutions to ionic and non-ionic detergents 73 . Each of these detergents has their own unique way of altering the structure and components of the cells as well as the three-dimensional structure of the ECM.…”
Section: Decellularization Strategiesmentioning
confidence: 99%